Hygroscopic motions of fossil conifer cones - Poppinga, Simon; Reible, Bruno (Scientific reports, 2017)
Conifer cones represent natural, woody compliant structures which move their scales as passive responses to changes in environmental humidity. Here we report on water-driven opening and closing motions in coalified conifer cones from the Eemian Interglacial (approx. 126,000-113,000 years BP) and from the Middle Miocene (approx. 16.5 to 11.5 million years BP). These cones represent by far the oldest documented evidence of plant parts showing full functionality of such passive hydraulically actuated motion. The functional resilience of these structures is far beyond the biological purpose of seed dispersal and protection and is because of a low level of mineralization of the fossils. Our analysis emphasizes the functional-morphological integrity of these biological compliant mechanisms which, in addition to their biological fascination, are potentially also role models for resilient and maintenance-free biomimetic applications (e.g., adaptive and autonomously moving structures including passive hydraulic actuators).
Gesehen am 23.10.2018